Employee-Centered Climate and organizational citizenship behaviors Affecting the commitment of car repair staff in Nakhon Pathom Province - Thiantha, Chuta; Thongrawd, Chairit; Tirawatdachochai, Bodinpat; Pan-in, Chalermpon (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
This research aims to 1. Study the commitment of car repair staff in Nakhon Pathom Province when classified by personal factors and 2. Study of Employee-Centered Climate and organizational citizenship behaviors affecting the commitment of car repair staff in Nakhon Pathom Province. The researcher collected 400 employees working in the car garage in Nakhon Pathom Province by convenient random sampling. Analyzed by percentage Mean,SD. One-way ANOVA Pearson correlation analysis and multiple regression analysis The research found that 1. Study the commitment of car garage employees in Nakhon Pathom province with different age and education level With statistical significance at the level of .05 2. Employee-Centered Climate that affects the commitment of the car garage staff in Nakhon Pathom Province, including providing independence in the operation X3 (b = 0.20). Commitment of car repair staff in Nakhon Pathom, namely as for organizational citizenship behaviors that affects the commitment of the car garage staff in Nakhon Pathom, such as Altruism X5 (b = 0.23) Consciousness X8 (b = 0.17) and Self-Development X11(b = 0.16) With all independent variables having 69 percent accuracy in forecasting and can write equations Commitment of car repair staff in Nakhon Pathom province as follows. Y=0.35+0.10X1+0.02X2+0.20X3*+0.02X4+0.23X5*+0.03X6+0.01X7+0.17X8*+0.07X9+0.04X10+0.16X11* Article history : Received 10 January 2019 Revised 24 April 2019 Accepted 30 April 2019 SIMILARITY INDEX = 1.23